2007
DOI: 10.1016/j.juro.2007.05.053
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bulbar Urethroplasty on Erectile Function

Abstract: We report on men undergoing 4 variations of bulbar urethroplasty. Although the numbers are small, we found that such surgery had an insignificant effect on erectile function. Surgical complexity with long stricture excision and the use of a buccal graft did not influence outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 7 publications
0
34
0
2
Order By: Relevance
“…While a nonmatched cohort of men undergoing circumcision was used as a control group, the authors did not find any significant difference in the two cohorts. There are four studies which evaluated erectile function by either IIEF [31], or IIEF-5 short form [7,32,33]; however, none has shown a significant difference. Using the Brief Male Sexual Function Inventory (BMSFI), Sharma et al [34] reported on a significant improvement in ejaculation and overall satisfaction in patients after anterior urethroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…While a nonmatched cohort of men undergoing circumcision was used as a control group, the authors did not find any significant difference in the two cohorts. There are four studies which evaluated erectile function by either IIEF [31], or IIEF-5 short form [7,32,33]; however, none has shown a significant difference. Using the Brief Male Sexual Function Inventory (BMSFI), Sharma et al [34] reported on a significant improvement in ejaculation and overall satisfaction in patients after anterior urethroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a small study size, Anger et al noted no appreciable change after urethral reconstruction. 11 The BMSFI instrument (erectile, ejaculatory, sexual drive) was subsequently used in 2 studies. 13,16 After preoperative exclusion of patients with conditions that impair erectile dysfunction, Sharma et al noted that postoperative improvements in ejaculation and overall satisfaction were most pronounced among men younger than 40 years old after anterior urethroplasty.…”
Section: Studies On Sexual Function Instrumentsmentioning
confidence: 99%
“…Studies by Palminteri et al, 12 Shenfeld et al, 13 Kessler et al, 14 Anger et al 15 and Nelson et al 16 concluded that there …”
Section: Discussionmentioning
confidence: 99%